IMPLEMENTASI KONSEP GOOD GOVERNANCE MELALUI MAL PELAYANAN PUBLIK DI KABUPATEN KOTABARU - Fadhel Muhammad; M Nur Iman Ridwan (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2026)
The background of this research stems from the local government’s efforts to realize governance that is transparent, accountable, effective, and oriented toward improving the quality of public services. This study aims to analyze the implementation of the concept of good governance through the operation of the Public Service Mall Mal (Pelayanan Publik or MPP) in Kotabaru Regency. The research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observations, and documentation involving implementing officials, partner agencies, and members of the public using MPP services. Data analysis was conducted using an interactive model involving data reduction, presentation, and conclusion drawing.The findings indicate that the application of good governance principles at the Kotabaru MPP has been carried out fairly well. Transparency is reflected in the openness of information and the use of digital systems; accountability is evident in the mechanisms of official responsibility; effectiveness and efficiency have improved through service integration and the use of information technology; and public participation is seen through feedback mechanisms. However, there are still challenges such as limited human resources, digital infrastructure constraints, and inter-agency coordination issues. Overall, the Kotabaru MPP has made a significant contribution to improving the quality of public services based on the principles of good governance.